2018
DOI: 10.1177/1747021818799240
|View full text |Cite
|
Sign up to set email alerts
|

Reversed effect of spatial compatibility when taking avatar’s perspective

Abstract: If an actor takes the perspective of an avatar, spatial dissociations could arise between the perspective of the actor and the perspective of the avatar. These become particularly interesting when solving spatial compatibility tasks. Effects of spatial compatibility are usually explained by a match or mismatch of automatic behavioural tendencies and intentional mapping processes. The question is whether actors develop such behavioural tendencies for an avatar and thereby are able to neglect their own perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…We used two different instructions for the same task to top–down influence perceived ownership of an avatar: the setup and the avatars used were similar to the ones of Böffel and Müsseler (2017) and Müsseler et al (2017) . The participants were confronted with an avatar that was displayed on a screen and sitting opposite them ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used two different instructions for the same task to top–down influence perceived ownership of an avatar: the setup and the avatars used were similar to the ones of Böffel and Müsseler (2017) and Müsseler et al (2017) . The participants were confronted with an avatar that was displayed on a screen and sitting opposite them ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This agency attribution seems to aide visual PT ( Zwickel, 2009 ). In past studies we showed that PT occurs toward avatars, regardless of whether PT is needed to complete the task ( Müsseler et al, 2017 ) or not ( Böffel and Müsseler, 2017 ). In the present study we confronted participants with an avatar that was presented opposite to them on a computer screen in a top–down view.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations